Phylogenetic Position of a Copper Age Sheep (Ovis aries) Mitochondrial DNA - Olivieri, Cristina; Ermini, Luca; Rizzi, Ermanno; Corti, Giorgio; Luciani, Stefania; Marota, Isolina; De Bellis, Gianluca; Rollo, Franco (PloS one, 2012)
Sheep (Ovis aries) were domesticated in the Fertile Crescent region about 9,000-8,000 years ago. Currently, few mitochondrial (mt) DNA studies are available on archaeological sheep. In particular, no data on archaeological European sheep are available. Here we describe the first portion of mtDNA sequence of a Copper Age European sheep. DNA was extracted from hair shafts which were part of the clothes of the so-called Tyrolean Iceman or Ötzi (5,350-5,100 years before present). Mitochondrial DNA (a total of 2,429 base pairs, encompassing a portion of the control region, tRNA(Phe), a portion of the 12S rRNA gene, and the whole cytochrome B gene) was sequenced using a mixed sequencing procedure based on PCR amplification and 454 sequencing of pooled amplification products. We have compared the sequence with the corresponding sequence of 334 extant lineages. A phylogenetic network based on a new cladistic notation for the mitochondrial diversity of domestic sheep shows that the Ötzi's sheep falls within haplogroup B, thus demonstrating that sheep belonging to this haplogroup were already present in the Alps more than 5,000 years ago. On the other hand, the lineage of the Ötzi's sheep is defined by two transitions (16147, and 16440) which, assembled together, define a motif that has not yet been identified in modern sheep populations.